OPTIMIZATION FOR EVOLUTIONARY CALCULATION - Raffo Lecca, Eduardo (2005)
The article presents the implementation of differential evolution algorithm in MATLAB® software. The price paid for an efficient numerical optimization, means to use of complex mathematics. The differential evolution is an exception because is easy to apply and robust in the numerical optimization. The differential evolution is a design tool of great utility in practical applications. The program presented in this article is an improved and efficient implementation of the program that present Price and Storm.